O elogio da ignorância : ascensão da extrema direita no Brasil após as eleições de 2018 - Jacques Neto, Carlos Oliveira (2022)
The neo-fascism that is spreading in the world, is it winning over the subjectivities of Brazilians to give flow to reactionary, slavers, discriminatory, individualists and antiscience feelings and attitudes, factors that feed hatred and the destruction of life and threaten thought, freedoms , humanist utopias and liberal democracies? The research work intends to analyze the historical and social conditions of the rise of fascism, elements that destroy social classes and transform them into masses, indifferent beings excluded from collective participation. We question what makes people cry out for the loss of their freedoms and to identify with demagogue leaders, who elect the destruction of workers' rights and guarantees and make the affront to republican and democratic institutions your death motto. The methodology used in this study is the dialectical view, a critical thought that interconnects knowledge and adopts a historical cognition of civilizing processes. Our premise is that, as beings of critical thinking, we are not spectators, but creators of history, not as we wish, but according to the material and social conditions of each time. We aim, in addition to understanding the social contradictions, to idealize an overcoming of problems through citizen and collective participatory action, a way of thinking about life as beyond subsistence, an existence of creation and development of subjective potentialities in the construction of paths of human emancipation. The research results confirm the advance of the extreme right movement in Brazil, the banalization of life and a subservience to the authoritarian, exploratory mentality and social exclusions, an accommodation to the existence of mediocrity, something that places subjects as the main agents of extinction. solidarity, nature and the human species. We identify in the person of Jair Bolsonaro a fascist reason, but incapable of managing an authoritarian or totalitarian State, since his greatest mark is the destitution of intellectual capacities, a being who is proud of his ignorance and the annihilation of a dignified life. Jair is not the problem, he is just the symptom and expression of exploitative elites and a retrograde middle class. We conclude that Bolsonaro will pass, but his followers will remain as potential supporters of a denialist leader. It is up to critical and enlightened thinking to unite with the revolutionary potential of the working classes and assume its condition of organic intellectual, working towards the creation of a new solidary, egalitarian, democratic society, towards the utopia of human emancipation.